Rapid array mapping of circadian clock and developmental mutations in Arabidopsis - Hazen, Samuel P. (2005)
Classical forward genetics, the identification of genes responsible for mutant phenotypes, remains an important part of functional characterization of the genome. With the advent of extensive genome sequence, phenotyping and genotyping remain the critical limiting variables in the process of map-based cloning. Here, we reduce the genotyping problem by hybridizing labeled genomic DNA to the Affymetrix Arabidopsis (Arabidopsis thaliana) ATH1 GeneChip. Genotyping was carried out on the scale of detecting greater than 8,000 single feature polymorphisms from over 200,000 loci in a single assay. By combining this technique with bulk segregant analysis, several high heritability development and circadian clock traits were mapped. The mapping accuracy using bulk pools of 26 to 100 F2 individuals ranged from 0.22 to 1.96 Mb of the mutations revealing mutant alleles of EARLY FLOWERING 3, EARLY FLOWERING 4, TIMING OF CAB EXPRESSION 1, and ASYMMETRIC LEAVES 1. While direct detection of small mutations, such as an ethyl-methane sulfonate derived single base substitutions, is limited by array coverage and sensitivity, large deletions such as those that can be caused by fast neutrons are easily detected. We demonstrate this by resolving two deletions, the 77-kb flavin-binding, kelch repeat, f-box 1 and the 7-kb cryptochrome2-1 deletions, via direct hybridization of mutant DNA to ATH1 expression arrays.